Materials science and technology :a comprehensive treatment /. Vollume 2A, Characterization of meterials part II / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Eric Lifshin - Lifshin, Eric
Vol. 2B Characterization of meterials part I in 1992